Large Firms and International Business Cycle Comovement - di Giovanni, Julian; Levchenko, Andrei A.; Mejean, Isabelle (American Economic Review, 2017)
This paper investigates the role of the top 100 firms in France in aggregate business cycle comovement. We establish that the top 100 firms (i) are important in aggregate; (ii) exhibit stronger international linkages than the rest of the economy; and (iii) contribute substantially to aggregate comovement.